Endogenous IL-33 inhibits apoptosis in non-small cell lung cancer cells by regulating BCL2/BAX via the ERK1/2 pathway - Liping Liu; Haoge Luo; Yingdong Xie; Ying Wang; Shiying Ren; Haiyang Sun; Zhuoyuan Xin; Dong Li (Scientific Reports)
Abstract Lung cancer remains a leading cause of cancer-related mortality worldwide, with non-small cell lung cancer (NSCLC) accounting for 85% of cases. Although targeted therapies have improved treatment outcomes, drug resistance poses a significant challenge, underscoring the need for novel therapeutic strategies. Interleukin-33 (IL-33), a member of the IL-1 superfamily, functions both as a nuclear protein and a cytokine, binding to its receptor, ST2. While IL-33 is known to promote tumour cell migration and metastasis, its role in regulating apoptosis remains incompletely understood. In this study, we focused on endogenous IL-33, employing lentiviral transfection to overexpress both the full-length and mature forms of IL-33 in lung cancer cells. We examined its effects on apoptosis in vitro and investigated the underlying molecular mechanisms. Our findings reveal that endogenous IL-33 inhibits apoptosis in lung cancer cells by modulating the expression of BCL2 and BAX via the ERK1/2 pathway in an autocrine manner. These results uncover a novel mechanism of IL-33-mediated tumour survival and provide a foundation for the development of IL-33/ST2-targeted therapies in NSCLC.